Viral impermeability of hypoallergenic, low protein, guayule latex films - Cornish K; Lytle C D (Journal of Biomedical Materials Research, 1999)
Guayule latex proteins do not cross-react with antibodies raised against latex proteins in commercially available products manufactured from Hevea brasiliensis latex. Thus guayule latex is a promising raw material for the manufacture of hypoallergenic latex products, safe for use by people suffering from IgE-medicated Type1 ;atex allergy. Guayule latex is also a low protein material and therefore unlikely to cause widespread sensitisation. Latex products commonly are used as essential barriers against the transmission of disease, and go guayule hypoallergenic latex medical products would be a viable alternative only if they possess effective viral barrier properties. To address this question, fingers of prototype hand-dipped guayule latex examinaiton gloves are tested for their permeability to a surrogate challenge virus. This virus has a diameter of 27 nm and is similar in size to the smallest human pathogenic viruses. Prototype guayule latex condom films are tested using synthetic blood over a range of pressures and, after four years of storage, with synthetic blood and with the virus. It is concluded that guayule latex films taken from prototype hand-dipped gloves and condoms provide effective barriers to virus transmission and that they remain effective (at least in condoms) after long-term storage.
Source Year: 2000
Keywords: Guayule latex films